Using entrepreneurship and social innovation to mitigate wealth inequality - Lyons, Thomas S.; Hamlin, Roger E.; Hamlin, Amanda (Boston : De/G Press, 2018)
Economic inequality continues to contribute to political and social instability around the world. This instability stifles development and results in widening the wealth gap between the "haves" and "have nots," further eroding stability. It has been argued that entrepreneurship is a prime contributor to this vicious cycle. Using Entrepreneurship and Social Innovation to Mitigate Wealth Inequality contends that this is only true when the opportunity for entrepreneurship is limited to a few. The authors maintain that when entrepreneurship is open to anyone who is properly motivated, innovative, and has a goal of growth for their enterprise, it helps build wealth for a greater number of people. The concept of "social entrepreneurship" is introduced, where entrepreneurship becomes a vehicle for explicitly addressing community-based economic and social challenges using markets. The book uses examples of entrepreneurial projects and programs that have attempted to address inequality to discuss entrepreneurship as an economic development strategy and its role in addressing the challenges of economic inequality. It advocates thinking and acting systemically, creating and sustaining entrepreneurial support ecosystems, in order to generate the synergy required to scale-up development and transform our economies and provides a distinctive perspective on a pressing social and economic issue, with significant implications for the future of the United States and the world.
Chapter 7: An Example from Michigan: The Michigan State University Product Center Food-Ag-Bio -- Chapter 8: An Example from Poland: The Warsaw Entrepreneurship Forum -- Chapter 9: Community Entrepreneurship: The Cases of the Lumber Enterprise in Ixtlan, Mexico, and the Pubs of Rural Ireland -- Chapter 10: Social Entrepreneurship among Native Peoples of the Americas: A Model or an Exception? -- Chapter 11: Necessary but Not Sufficient: Only Systemic Approaches Transform -- Index.
Includes bibliographical references and index.
Keywords: Social entrepreneurship; Entrepreneurship -- Economic aspects; Income distribution; Entrepreneurship -- Economic aspects; Income distribution; Social entrepreneurship